Temporal characteristics and associated factors of discontinuation and outcomes after percutaneous coronary intervention - Xu, Haiyan; Zheng, Wanxiang; Tan, Jiangqin; Li, Min (Frontiers in Pharmacology, 2024)
Background: Medication adherence in patients after percutaneous coronary intervention (PCI) is suboptimal, and discontinuation is common. Information on the temporal characteristics and associated factors of discontinuation and outcomes after PCI is insufficient to improve medication adherence interventions. Methods: We conducted a single-center retrospective study of post-PCI patients by telephone survey and medical record extraction. Temporal characteristics and associated factors of discontinuation and outcomes were examined by survival curve analysis, Cox regression, or time-dependent Cox regression. Results: Discontinuation and major adverse cardiovascular events (MACE) after PCI had similar temporal characteristics, with the highest incidence in the first year, followed by a decline. Temporary discontinuation was associated with pre-PCI medication nonadherence (HR 1.63; 95% CI: 1.09–2.43), lack of medication necessity (HR 2.33; 95% CI: 1.44–3.78), economic difficulties (HR 2.09; 95% CI: 1.26–3.47), routine disruption (HR 2.09; 95% CI: 1.10–3.99), and emotional distress (HR 2.76; 95% CI: 1.50–5.09). Permanent discontinuation was associated with residence in rural areas (HR 4.18; 95% CI: 1.84–9.46) or small to medium-sized cities (HR 4.21; 95% CI: 1.82–9.73), lack of medication necessity (HR 10.60; 95% CI: 6.45–17.41), and side effects (HR 3.30; 95% CI: 1.94–5.62). The MACE after PCI was associated with pre-PCI hypertension (HR 1.42; 95% CI: 1.04–1.96), two coronary stents (HR 1.42; 95% CI: 1.01–1.99) or three coronary stents (HR 1.66; 95% CI: 1.11–2.49) compared to one coronary stent up to this PCI, and temporary discontinuation (≤60 months HR 2.18; 95% CI: 1.47–3.25; >60 months HR 8.82; 95% CI: 3.65–21.28). Conclusion: Discontinuation and MACE after PCI have similar temporal characteristics, temporary discontinuation and permanent discontinuation have different associated factors, and the former is associated with MACE. These findings may provide guidance for medication adherence interventions.